2017
DOI: 10.4093/dmj.2017.41.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Physician-Directed Diabetes Education without a Medication Change and Associated Patient Outcomes

Abstract: BackgroundWhen patients with diabetes mellitus (DM) are first referred to a hospital from primary health care clinics, physicians have to decide whether to administer an oral hypoglycemic agent (OHA) immediately or postpone a medication change in favor of diabetes education regarding diet or exercise. The aim of this study was to determine the effect of diabetes education alone (without alterations in diabetes medication) on blood glucose levels.MethodsThe study was conducted between January 2009 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Our team has conducted several studies on RWE and has built various CDMs [8, 15, 19, 26], but many methodological errors remain to be corrected. In many existing RWEs, it is often the case that a large sample size offers an appealing advantage over RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Our team has conducted several studies on RWE and has built various CDMs [8, 15, 19, 26], but many methodological errors remain to be corrected. In many existing RWEs, it is often the case that a large sample size offers an appealing advantage over RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle management, including diabetes self-management education, nutrition therapy, and physical activity, is a fundamental aspect of the successful management of diabetes [ 1 , 2 ]. Previous studies [ 1 ] have demonstrated that diabetes self-management education improves self-management, diabetes knowledge, satisfaction and quality of life, and glycemic control, and also reduces health care costs.…”
Section: Introductionmentioning
confidence: 99%